2010
DOI: 10.1111/j.1365-2478.2010.00870.x
|View full text |Cite
|
Sign up to set email alerts
|

Test of rock physics models for prediction of seismic velocities in shallow unconsolidated sands: a well log data case

Abstract: A B S T R A C TThis paper tests the ability of various rock physics models to predict seismic velocities in shallow unconsolidated sands by comparing the estimates to P and S sonic logs collected in a shallow sand layer and ultrasonic laboratory data of an unconsolidated sand sample. The model fits are also evaluated with respect to the conventional model for unconsolidated sand. Our main approach is to use Hertz-Mindlin and Walton contact theories, assuming different weight fractions of smooth and rough conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 20 publications
(39 reference statements)
0
7
0
Order By: Relevance
“…Bachrach, Dvorkin and Nur (), Zimmer et al . (2007a,b), Walton (), Andersen and Johansen () and Moyano et al . () have discussed rock physics of underconsolidated sediments.…”
Section: Estimation Of Seabed Propertiesmentioning
confidence: 98%
“…Bachrach, Dvorkin and Nur (), Zimmer et al . (2007a,b), Walton (), Andersen and Johansen () and Moyano et al . () have discussed rock physics of underconsolidated sediments.…”
Section: Estimation Of Seabed Propertiesmentioning
confidence: 98%
“…). Andersen and Johansen () showed that the velocities calculated from a combination of this model and Hashin–Shtrikman lower bound interpolation give a good agreement with acquired log‐derived acoustic velocity measurements from shallow unconsolidated gas sand. Although the calculated dry elastic moduli are close to the measured values, still, the dry elastic moduli are slightly overestimated by the contact models.…”
Section: Discussionmentioning
confidence: 77%
“…The validity and applicability of these contact models have been discussed in several studies, and some modifications are suggested (Bachrach, Dvorkin, and Nur ; Zimmer et al . ; Andersen and Johansen ; Dutta, Mavko, and Mukerji ). Moreover, the friable sand model developed by Dvorkin and Nur () can describe the effect of sorting on dry effective elastic properties of unconsolidated sands, and the model helps to predict rock properties at porosities between zero (non‐porous mineral phase) and initial depositional porosity (critical porosity).…”
Section: Introductionmentioning
confidence: 99%
“…The moduli increase more rapidly in Makse et al's (1999) model because the number of grain contacts is also increasing with pressure. Recently, Andersen and Johansen (2010) found that Walton's (1987) model overpredicts the observed sonic log wave speeds in unconsolidated sands by more than a factor of 1.5, and they suggested empirically derived curves (e.g., Fam and Santamarina, 1997) may be best. Although the theory illustrated in Figure 21 captures some of the elements of the pressure dependence of the moduli, real measurements on granular materials give different moduli and velocities (Hardin and Blandford, 1989).…”
Section: Pressure Dependence In Granular Materialsmentioning
confidence: 99%